On the divergence of Fourier series in the general Haar system - Grigoryan, Martin; Maranjyan, Artavazd (Armenian Journal of Mathematics, 2021)
For any countable set D [0,1], we construct a bounded measurable function f such that the Fourier series of f with respect to the regular general Haar system is divergent on D and convergent on [0,1]D.